Polymer microsphere and preparation method thereof, composite diaphragm and battery
By using polymer microspheres as the diaphragm coating, the core layer bonding material is released and bonded to the electrode sheet using normal temperature pressure, the problem of high-temperature hot pressing bonding and adhesion of the diaphragm and the electrode sheet is solved, and the diaphragm is adhered when the diaphragm is coiled is achieved. Improved battery interface performance.
Patent Information
- Application Number
- CN202411523360.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
The existing diaphragm and the pole sheet need to be bonded at high temperature, and adhesion is prone to occur during the winding of the diaphragm, resulting in battery interface problems.
Polymer microspheres are used as the diaphragm coating. The polymer microspheres are composed of a core and shell. The core is an acrylic polymer and the shell is an elastic material with a porous structure. The core layer bonding material is released through normal temperature pressure and bonded to the electrode sheet. .
The firm bond between the diaphragm and the electrode sheet can be achieved without high-temperature hot pressing, reducing production costs and safety risks, avoiding adhesion problems during diaphragm winding, and improving battery interface performance.
Smart Images

Figure CN119391011A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a polymer microsphere and a preparation method thereof, a composite separator and a battery. Background Art
[0002] In the field of battery technology, the diaphragm is a key component, which plays the role of isolating the positive and negative electrodes, preventing short circuits, and allowing ions to pass through, thereby achieving normal operation of the battery. However, the bonding effect between the diaphragm and the pole piece has an important impact on the performance of the battery. If the bonding between the diaphragm and the pole piece is not strong, it may cause battery interface problems, such as increased interface impedance, decreased battery capacity, and shortened cycle life. Therefore, how to improve the bonding effect between the diaphragm and the pole piece has become one of the important research directions in the field of battery manufacturing.
[0003] By coating the surface of the diaphragm with a polymer coating, the performance of the diaphragm can be improved, such as improving its thermal stability and improving its bonding effect with the pole piece. However, traditional polymer coatings need to be hot-pressed at high temperatures to achieve bonding with the pole piece, which not only increases production costs, but also increases safety risks in the production process. In addition, when manufactured at high temperatures, the puncture strength of the diaphragm is greatly reduced, causing the battery short circuit rate to increase significantly. Although some materials can be bonded at room temperature, there is also a certain stress in the diaphragm winding process, which causes the diaphragm to stick during winding and cannot be unwound. Summary of the invention
[0004] The purpose of the present application is to provide a polymer microsphere and a preparation method thereof, a composite diaphragm and a battery, aiming to solve the problem that the existing diaphragm and the pole piece need to be bonded at high temperature and hot pressed, and adhesion occurs during the diaphragm winding process.
[0005] To achieve the above objectives, the present application provides a polymer microsphere for a battery separator, wherein the polymer microsphere comprises a core and a shell covering the core, wherein the core comprises an acrylic polymer, the shell comprises an elastic material, the shell is a porous structure, and the pores at least partially penetrate two opposite sides of the shell.
[0006] In some embodiments, at least one of the following conditions is met:
[0007] A. The Tg of the acrylic polymer is -20°C to 60°C;
[0008] Optionally, the Tg of the acrylic polymer is 0°C to 20°C;
[0009] B. The particle size D50 of the core is 0.5 μm to 3 μm;
[0010] C. the acrylic polymer is selected from at least one of polymethacrylate, polyacrylic acid, polyacrylonitrile and polyvinyl acrylate;
[0011] D. The elastic material is selected from at least one of polydimethylsiloxane, polyurethane, polyacrylic acid, styrene-ethylene-butylene copolymer, and methacrylate polymer.
[0012] In some embodiments, the acrylic polymer is selected from polymethacrylate; and the elastic material is selected from polydimethylsiloxane or styrene-ethylene-butylene copolymer.
[0013] The present application also provides a method for preparing the polymer microspheres as described above, comprising:
[0014] Adding the elastic material solution to the acrylic polymer solution, mixing evenly, and keeping the mixture warm, so that the elastic material self-assembles on the surface of the acrylic polymer to obtain the polymer microspheres;
[0015] Alternatively, the monomer corresponding to the elastic material is added to an acrylic polymer solution, mixed evenly, and kept warm to allow the monomer to polymerize on the surface of the acrylic polymer to form the elastic material, thereby obtaining the polymer microspheres.
[0016] In some embodiments, at least one of the following conditions is met:
[0017] A. The mass ratio of the elastic material to the acrylic polymer is (0.1-1):10;
[0018] Optionally, the mass ratio of the elastic material to the acrylic polymer is (0.1-0.5):10;
[0019] B. The mass ratio of the monomer corresponding to the elastic material to the acrylic polymer is (0.1-1):10;
[0020] C. The insulation temperature is 30°C to 100°C.
[0021] In some embodiments, the elastic material further comprises introducing a pore-forming agent during the self-assembly process on the acrylic polymer surface, and the preparation method satisfies at least one of the following conditions:
[0022] A. The pore forming agent is carbon dioxide;
[0023] Optionally, the flow rate of the carbon dioxide is 10 to 100 mL / min;
[0024] Further optionally, the flow rate of the carbon dioxide is 10 to 50 mL / min;
[0025] B. The mass ratio of the elastic material to the acrylic polymer is (0.1-2):10.
[0026] The present application also provides a composite diaphragm, comprising a substrate and a coating disposed on the substrate, wherein the raw material of the coating comprises the polymer microspheres as described above.
[0027] In some embodiments, the slurry for preparing the coating includes, by weight: 5-50 parts of polymer microspheres, 0.1-15 parts of a binder, 0-5 parts of a dispersant, and 0.01-5 parts of a wetting agent;
[0028] The composite diaphragm satisfies at least one of the following conditions:
[0029] A. The substrate comprises at least one of polyethylene, polypropylene, polyimide, aramid, and cellulose;
[0030] B. The adhesive comprises at least one of polyacrylonitrile, styrene-butadiene rubber, sodium hydroxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, polyacrylate, and polyacrylamide;
[0031] C. the dispersant comprises at least one of ammonium polyacrylate, sodium hexametaphosphate, and sodium pyrophosphate;
[0032] D. the wetting agent comprises at least one of alkyl sulfate, sulfonate, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether and organosiloxane;
[0033] E. The coating preparation method includes at least one of spraying, spot coating and roller coating.
[0034] The present application also provides a battery, comprising a pole piece and the composite diaphragm as described above bonded to the pole piece.
[0035] In some embodiments, the bonding temperature between the pole piece and the composite separator is above 15°C.
[0036] Compared with the prior art, the beneficial effects of this application include:
[0037] The polymer microspheres provided in the present application include a core and a shell, wherein the core acrylic polymer is a bonding material and the shell is a porous structure, making it similar to a cage structure. The polymer microspheres are applied to battery diaphragms as a polymer coating. During the normal temperature and pressure process, the bonding material of the core layer is released from the pore structure of the shell layer due to pressure, so that it is bonded to the pole piece without the need for high-temperature hot pressing, thereby greatly reducing production costs and improving production safety; since the bonding material of the core-shell structured polymer microspheres is in the core layer, the problem of adhesion when the diaphragm is rolled up will not be caused; the core-shell structured polymer coating can effectively improve the bonding effect between the diaphragm and the pole piece, thereby solving the battery interface problem caused by the weak bonding between the diaphragm and the pole piece in the traditional technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0039] Figure 1 This is a scanning electron microscope photograph of the composite membrane obtained in Example 2;
[0040] Figure 2 This is a scanning electron microscope photograph of the composite diaphragm obtained in Comparative Example 2. DETAILED DESCRIPTION
[0041] As used herein:
[0042] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0043] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0044] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0045] In these examples, parts and percentages are by mass unless otherwise indicated.
[0046] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0047] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0048] The present application provides a polymer microsphere for a battery separator, wherein the polymer microsphere comprises a core and a shell covering the core, wherein the core comprises an acrylic polymer, the shell comprises an elastic material, the shell is a porous structure, and the pores at least partially penetrate two opposite sides of the shell.
[0049] The two opposite sides of the shell refer to the side close to the core and the surface of the polymer microsphere. The core acrylic polymer is the bonding material, and the shell is a porous structure, which is similar to a cage structure. The polymer microsphere is applied to the battery diaphragm as a polymer coating. During the normal temperature pressure process, the bonding material of the core layer is released from the pore structure of the shell layer due to pressure, so that it can be bonded to the pole piece without high temperature hot pressing, thereby greatly reducing the production cost and improving production safety; because the bonding material of the core-shell structure polymer microsphere is in the core layer, it will not cause the problem of adhesion when the diaphragm is rolled up; the core-shell structure polymer coating can effectively improve the bonding effect between the diaphragm and the pole piece, thereby solving the battery interface problem caused by the weak bonding between the diaphragm and the pole piece in the traditional technology.
[0050] Among them, the porous structure of the shell can be the pores obtained by the pore-forming agent, or the amount of elastic material used in the shell is low, so that the elastic material cannot completely cover the inner core, forming an incompletely covered shell layer, and the area not covered by the elastic material forms a pore-like structure.
[0051] In some embodiments, the Tg of the acrylic polymer is -20°C to 60°C, for example, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C or any value between -20°C and 60°C.
[0052] If the Tg of the acrylic polymer is too low, its cohesion is poor and it is easy to swell and dissolve in the electrolyte; if the Tg of the acrylic polymer is too high, it is impossible to achieve room temperature bonding. Optionally, the Tg of the acrylic polymer is 0°C to 20°C.
[0053] In some embodiments, the particle size D50 of the inner core is 0.5 μm to 3 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any value between 0.5 μm and 3 μm.
[0054] If the particle size D50 of the core is too large, the coating will be too thick when preparing the composite diaphragm, which is not conducive to improving the battery energy density. If the particle size D50 of the core is too small, it will easily block the pores of the diaphragm, which is not conducive to ion transmission.
[0055] In some embodiments, the acrylic polymer is selected from at least one of polymethacrylate, polyacrylic acid, polyacrylonitrile, and polyvinyl acrylate. Polymethacrylate may be, for example, polymethyl methacrylate (PMMA), polyethyl methacrylate, polypropyl methacrylate, and the like.
[0056] In some embodiments, the elastic material is selected from at least one of polydimethylsiloxane (PDMS), polyurethane, polyacrylic acid (PAA), styrene-ethylene-butylene copolymer (SEBS), and methacrylate polymers.
[0057] Among them, the methacrylate polymer can be obtained by polymerizing methacrylate monomers, such as methyl methacrylate (MMA), ethyl methacrylate, propyl methacrylate, etc. The methacrylate polymer can also be obtained by polymerizing methacrylate monomers and other comonomers, and the other comonomers can be, for example, styrene.
[0058] In some embodiments, the acrylic polymer is selected from polymethacrylate; and the elastic material is selected from polydimethylsiloxane or styrene-ethylene-butylene copolymer.
[0059] The present application also provides a method for preparing the above-mentioned polymer microspheres, comprising:
[0060] Adding the elastic material solution to the acrylic polymer solution, mixing evenly, and keeping the mixture warm, so that the elastic material self-assembles on the surface of the acrylic polymer to obtain the polymer microspheres;
[0061] Alternatively, the monomer corresponding to the elastic material is added to an acrylic polymer solution, mixed evenly, and kept warm to allow the monomer to polymerize on the surface of the acrylic polymer to form the elastic material, thereby obtaining the polymer microspheres.
[0062] Among them, the elastic material can be polydimethylsiloxane, polyurethane, polyacrylic acid, styrene-ethylene-butylene copolymer or methacrylate polymer, etc.; when the elastic material is polydimethylsiloxane, polyurethane, polyacrylic acid, styrene-ethylene-butylene copolymer, it can be directly added to the acrylic polymer solution for self-assembly; when the elastic material is a methacrylate polymer, the monomer of the methacrylate polymer needs to be added to the acrylic polymer solution for polymerization to form the elastic material.
[0063] The monomers of the methacrylate polymer can be methyl methacrylate, ethyl methacrylate or propyl methacrylate, or a mixture of methyl methacrylate, ethyl methacrylate or propyl methacrylate and styrene; the monomers are polymerized to form the elastic material methacrylate polymer.
[0064] In some embodiments, the mass ratio of the elastic material to the acrylic polymer is (0.1-1):10, for example, it can be 0.1:10, 0.2:10, 0.3:10, 0.4:10, 0.5:10, 0.6:10, 0.7:10, 0.8:10, 0.9:10, 1:10 or any ratio between (0.1-1):10.
[0065] The amount of elastic material used in the outer shell is relatively low, so that the elastic material cannot completely cover the acrylic polymer core, forming an incompletely covered shell layer, and the area not covered by the elastic material forms a channel-like structure.
[0066] If the amount of elastic material used is too little, it will not be enough to cover the acrylic polymer core, resulting in excessive bonding strength between the diaphragms and self-adhesion of the diaphragms; if the amount of elastic material used is too much, the shell layer formed will be too thick, resulting in insufficient bonding strength between the diaphragm and the electrode.
[0067] Optionally, the mass ratio of the elastic material to the acrylic polymer is (0.1-0.5):10.
[0068] Similarly, the mass ratio of the monomer corresponding to the elastic material to the acrylic polymer is (0.1-1):10.
[0069] In some embodiments, the insulation temperature is 30°C-100°C, for example, it can be 30°C, 35°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value between 30°C-100°C.
[0070] In some embodiments, the elastic material further comprises introducing a pore-forming agent during the self-assembly process on the acrylic polymer surface, so that the prepared elastic material shell layer has pores, and the pore-forming agent is carbon dioxide.
[0071] In some embodiments, the flow rate of the carbon dioxide is 10 to 100 mL / min, for example, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, 100 mL / min or any value between 10 and 100 mL / min. Optionally, the flow rate of the carbon dioxide is 10 to 50 mL / min.
[0072] If the flow rate of carbon dioxide is too high, the pores formed in the outer shell will be too many and too large, increasing the adhesion between the diaphragms; if the flow rate of carbon dioxide is too low, the pores formed in the outer shell will be insufficient, and the adhesive material of the inner core cannot be released during the extrusion process, reducing the bonding strength with the electrode.
[0073] In some embodiments, the mass ratio of the elastic material to the acrylic polymer is (0.1-2):10, for example, 0.1:10, 0.2:10, 0.3:10, 0.4:10, 0.5:10, 0.6:10, 0.7:10, 0.8:10, 0.9:10, 1:10, 1.1:10, 1.2:10, 1.3:10, 1.4:10, 1.5:10, 1.6:10, 1.7:10, 1.8:10, 1.9:10, 2:10 or any ratio between (0.1-2):10. In this embodiment, since the pores of the shell are obtained by the pore forming agent, the amount of the elastic material can be higher.
[0074] The present application also provides a composite diaphragm, comprising a substrate and a coating disposed on the substrate, wherein the raw material of the coating comprises the polymer microspheres as described above.
[0075] In some embodiments, the polymer microspheres are formulated into a slurry, and the slurry comprises, by weight, 5-50 parts of polymer microspheres, 0.1-15 parts of a binder, 0-5 parts of a dispersant, and 0.01-5 parts of a wetting agent.
[0076] In some embodiments, the substrate includes at least one of polyethylene, polypropylene, polyimide (PI), aramid, and cellulose.
[0077] In some embodiments, the adhesive includes at least one of polyacrylonitrile, styrene-butadiene rubber (SBR), sodium hydroxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, polyacrylate, and polyacrylamide.
[0078] In some embodiments, the dispersant includes at least one of ammonium polyacrylate, sodium hexametaphosphate, and sodium pyrophosphate.
[0079] In some embodiments, the wetting agent includes at least one of alkyl sulfates, sulfonates, polyoxyethylene alkylphenol ethers, polyoxyethylene fatty alcohol ethers, and organosiloxanes.
[0080] In some embodiments, the coating is prepared by at least one of spraying, spot coating, and roller coating.
[0081] The present application also provides a battery, comprising a pole piece and the composite diaphragm as described above bonded to the pole piece.
[0082] The electrode sheet includes a positive electrode sheet and a negative electrode sheet, and the composite separator is arranged between the positive electrode sheet and the negative electrode sheet. The active material of the positive electrode sheet can be lithium iron phosphate (LFP) or a ternary material.
[0083] In some embodiments, the bonding temperature between the pole piece and the composite separator is above 15°C, for example, 15°C-30°C.
[0084] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0085] Example 1
[0086] Embodiment 1 First, a polymer microsphere is provided, and its preparation method comprises the following steps:
[0087] PMMA (Tg = 20 ° C) with a particle size of 1 μm was dispersed in an aqueous solution by adding 1% emulsifier, and 10g PDMS was dissolved in a certain amount of tetrahydrofuran (THF) to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 0.5:10 (solid to solid PDMS: PMMA), and stirred while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 100 mL / min, and carbon dioxide formed micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 hour to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 1.
[0088] Example 1 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 1. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0089] Example 2
[0090] Embodiment 2 First, a polymer microsphere is provided, and its preparation method comprises the following steps:
[0091] PMMA (Tg = 20 ° C) with a particle size of 1 μm was dispersed in an aqueous solution by adding 1% emulsifier, and 10g PDMS was dissolved in a certain amount of THF to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 0.5:10 (solid to solid PDMS: PMMA), stirring while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 50 mL / min. Carbon dioxide forms micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 hour to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 2.
[0092] Example 2 also provides a composite membrane, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the membrane by spraying, and dried at 80°C to obtain the composite membrane of Example 2. The scanning electron microscope photograph of the composite membrane of Example 2 is as shown in Figure 1 shown. Figure 1 In order to realize the surface pore structure, the shell layer forms a multi-level rough structure. This rough surface has no adhesive force, which can prevent adhesion during the membrane winding process. At the same time, the adhesive material of the core layer can be squeezed out by pressure to bond with the pole piece. After cold pressing with the LFP pole piece for 60s at 3MPa and 25℃, the bonding strength between the composite membrane and the pole piece is tested using a tensile testing machine.
[0093] Example 3
[0094] Embodiment 3 Firstly, a polymer microsphere is provided, and its preparation method comprises the following steps:
[0095] PMMA (Tg = 20 ° C) with a particle size of 1 μm was dispersed in an aqueous solution by adding 1% emulsifier, and 10g PDMS was dissolved in a certain amount of THF to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 2:10 (solid to solid PDMS: PMMA), and stirred while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 50 mL / min. Carbon dioxide forms micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 hour to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 3.
[0096] Example 3 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 3. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0097] Example 4
[0098] Embodiment 4 First, a polymer microsphere is provided, and its preparation method comprises the following steps:
[0099] PMMA (Tg = 20 ° C) with a particle size of 1 μm was dispersed in an aqueous solution by adding 0.5% emulsifier, and 10g PDMS was dissolved in a certain amount of THF to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 1:10 (solid to solid PDMS: PMMA), and stirred while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 100 mL / min, and carbon dioxide formed micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 hour to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 4.
[0100] Example 4 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 4. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0101] Example 5
[0102] Embodiment 5 First, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0103] PMMA (Tg = 0 ° C) with a particle size of 1.5 μm was dispersed in an aqueous solution by adding 0.5% emulsifier, and 10 g of PDMS was dissolved in a certain amount of THF to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 1:10 (solid to solid PDMS: PMMA), and stirred while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 30 mL / min, and carbon dioxide formed micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 h to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 5.
[0104] Example 5 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 5. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0105] Example 6
[0106] Embodiment 6 First, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0107] PMMA (Tg = 0 ° C) with a particle size of 1.5 μm was dispersed in an aqueous solution by adding 0.5% emulsifier, and 10 g of PDMS was dissolved in a certain amount of THF to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 2:10 (solid to solid PDMS: PMMA), and stirred while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 30 mL / min, and carbon dioxide formed micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 hour to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 6.
[0108] Example 6 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 6. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0109] Example 7
[0110] Embodiment 7 Firstly, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0111] PMMA (Tg = 0 ° C) with a particle size of 2 μm was dispersed in an aqueous solution by adding 0.3% emulsifier, and 10g PDMS was dissolved in a certain amount of THF to obtain its polymer solution. The PDMS solution was slowly added to the PMMA solution at a mass ratio of 2:10 (solid to solid PDMS: PMMA), and stirred while adding to ensure uniform mixing. The mixed solution was placed in a constant temperature water bath, and the temperature was controlled at 40 ° C. Under this condition, PDMS gradually self-assembled to form a core-shell structure with PMMA as the core and PDMS as the shell. During the self-assembly process, carbon dioxide gas was continuously introduced at a flow rate of 10 mL / min, and carbon dioxide formed micropores in the PDMS phase. The self-assembled system was maintained at 40 ° C for 1 hour to ensure that PDMS was fully cured to form a stable pore structure. Afterwards, the solvent and unreacted monomers in the system were removed by vacuum drying and other methods to obtain the polymer microspheres of Example 7.
[0112] Example 7 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 0.5 parts of adhesive, 0.1 parts of wetting agent, and 89.4 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 7. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0113] Example 8
[0114] Embodiment 8 First, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0115] Add 1% emulsifier to PMMA (Tg = 0°C) with a particle size of 1 μm to disperse it in an aqueous solution, and dissolve 10g of SEBS in a certain amount of acetone to obtain its polymer solution. Slowly add the SEBS solution to the PMMA solution at a mass ratio of 1:10 (solid to solid SEBS: PMMA), stirring while adding to ensure uniform mixing. The mixed solution is placed in a constant temperature water bath and the temperature is controlled at 35°C. Under this condition, SEBS gradually self-assembles to form a core-shell structure with PMMA as the core and SEBS as the shell. After the self-assembly process, the solvent in the system is removed by vacuum drying and the like to obtain the polymer microspheres of Example 8.
[0116] Example 8 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 1 part of adhesive, 0.05 parts of wetting agent, and 88.95 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 8. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0117] Example 9
[0118] Embodiment 9 First, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0119] Add 1% emulsifier to PMMA (Tg = 0°C) with a particle size of 1 μm to disperse it in an aqueous solution, and dissolve 10g of SEBS in a certain amount of acetone to obtain its polymer solution. Slowly add the SEBS solution to the PMMA solution at a mass ratio of 0.1:10 (solid to solid SEBS: PMMA), stirring while adding to ensure uniform mixing. The mixed solution is placed in a constant temperature water bath and the temperature is controlled at 35°C. Under this condition, SEBS gradually self-assembles to form a core-shell structure with PMMA as the core and SEBS as the shell. After the self-assembly process, the solvent in the system is removed by vacuum drying and the like to obtain the polymer microspheres of Example 9.
[0120] Example 9 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 1 part of adhesive, 0.05 parts of wetting agent, and 88.95 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 9. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0121] Example 10
[0122] Embodiment 10 Firstly, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0123] Add 1% emulsifier to PMMA (Tg = 0°C) with a particle size of 1 μm to disperse it in an aqueous solution, and dissolve 10g of SEBS in a certain amount of acetone to obtain its polymer solution. Slowly add the SEBS solution to the PMMA solution at a mass ratio of 0.5:10 (solid to solid SEBS: PMMA), stirring while adding to ensure uniform mixing. The mixed solution is placed in a constant temperature water bath and the temperature is controlled at 35°C. Under this condition, SEBS gradually self-assembles to form a core-shell structure with PMMA as the core and SEBS as the shell. After the self-assembly process, the solvent in the system is removed by vacuum drying and the like to obtain the polymer microspheres of Example 10.
[0124] Example 10 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 1 part of adhesive, 0.05 parts of wetting agent, and 88.95 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 10. After cold pressing with the LFP pole piece at 3MPa and 25°C for 60s, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0125] Embodiment 11
[0126] Embodiment 11 Firstly, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0127] Add 5% water-soluble initiator to PMMA (Tg = 20°C) with a particle size of 1 μm, add 0.1g of MMA monomer, place the mixed solution in a constant temperature water bath, control the temperature at 80°C, and stir at a speed of 500 r / min to avoid agglomeration to obtain a colloidal emulsion. After the reaction process, remove the solvent in the system by vacuum drying and other methods to obtain the polymer microspheres of Example 11, PMMA with a core-shell structure.
[0128] Example 11 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 1 part of adhesive, 0.05 parts of wetting agent, and 88.95 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 11. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0129] Example 12
[0130] Embodiment 12 Firstly, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0131] Add 5% water-soluble initiator to PMMA (Tg = 20°C) with a particle size of 1 μm, and add 0.1g of MMA and styrene monomer (the mass ratio of MMA and styrene is 0.1:10). Place the mixed solution in a constant temperature water bath, control the temperature at 90°C, and stir at a speed of 500 r / min to avoid agglomeration to obtain a colloidal emulsion. After the reaction process, remove the solvent in the system by vacuum drying or the like to obtain the polymer microspheres of Example 12, PMMA with a core-shell structure.
[0132] Example 12 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 1 part of adhesive, 0.05 parts of wetting agent, and 88.95 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 12. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0133] Example 13
[0134] Embodiment 13 Firstly, a polymer microsphere is provided, and the preparation method thereof comprises the following steps:
[0135] Add 5% water-soluble initiator to PMMA (Tg = 20°C) with a particle size of 1 μm, and add 0.05g of MMA and styrene monomer (the mass ratio of MMA and styrene is 0.05:10). Place the mixed solution in a constant temperature water bath, control the temperature at 80°C, and stir at a speed of 1000 r / min to avoid agglomeration to obtain a colloidal emulsion. After the reaction process, remove the solvent in the system by vacuum drying or the like to obtain the polymer microspheres of Example 13, PMMA with a core-shell structure.
[0136] Example 13 also provides a composite diaphragm, wherein the prepared polymer microspheres include the following components by mass: 10 parts of polymer microspheres, 1 part of adhesive, 0.05 parts of wetting agent, and 88.95 parts of water, and are configured into a slurry, which is applied on the diaphragm by spraying, and dried at 80°C to obtain the composite diaphragm of Example 13. After cold pressing with the LFP pole piece for 60s at 3MPa and 25°C, the bonding strength between the composite diaphragm and the pole piece is tested using a tensile testing machine.
[0137] Comparative Example 1
[0138] The polymer microspheres in this comparative example are commercially available PMMA (Tg=50° C.) with a particle size of 1 μm. The preparation of the composite membrane is the same as in Example 1.
[0139] Comparative Example 2
[0140] In this comparative example, PMMA without a shell layer in Example 1 is used as polymer microspheres. The preparation of the composite membrane is the same as in Example 1. The scanning electron microscope photo of the composite membrane of Comparative Example 2 is shown in FIG. Figure 2 As shown, it can be seen that conventional PMMA is a spherical structure with a smooth surface and has its own adhesive strength. While achieving room temperature bonding, it is easy to have self-adhesion problems.
[0141] Test of bonding strength between diaphragms: The composite diaphragms of the above-mentioned embodiments / comparative examples were double-layered, respectively, and after pressing for 60 seconds at 1 MPa and 25° C., the bonding strength between the composite diaphragms was tested using a tensile testing machine.
[0142] The physical parameters of the polymer microspheres of each embodiment and comparative example, as well as the bonding strength between the composite diaphragm and the pole piece, and the bonding strength with the diaphragm are shown in Table 1. According to Table 1, the bonding strength between the composite diaphragms of Examples 1 to 13 of the present application and the pole piece at room temperature is higher than that of Comparative Example 1, and the bonding strength with the diaphragm is lower than that of Comparative Example 2, which proves that the composite diaphragm of the present application can be firmly bonded to the pole piece at room temperature, and will not cause adhesion when the diaphragm is rolled up.
[0143] Table 1 Physical parameters and test data of polymer microspheres of various embodiments and comparative examples
[0144]
[0145]
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0147] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A polymer microsphere for battery separator, characterized in that: The polymer microsphere comprises a core and a shell covering the core, wherein the core comprises an acrylic polymer, the shell comprises an elastic material, the shell is a porous structure, and the pores at least partially penetrate two opposite surfaces of the shell.
2. The polymer microsphere according to claim 1, characterized in that At least one of the following conditions is met: A. The Tg of the acrylic polymer is -20°C to 60°C; Optionally, the Tg of the acrylic polymer is 0°C to 20°C; B. The particle size D50 of the core is 0.5 μm to 3 μm; C. the acrylic polymer is selected from at least one of polymethacrylate, polyacrylic acid, polyacrylonitrile and polyvinyl acrylate; D. The elastic material is selected from at least one of polydimethylsiloxane, polyurethane, polyacrylic acid, styrene-ethylene-butylene copolymer, and methacrylate polymer.
3. The polymer microsphere according to claim 2, characterized in that The acrylic polymer is selected from polymethacrylate; the elastic material is selected from polydimethylsiloxane or styrene-ethylene-butylene copolymer.
4. A method for preparing polymer microspheres according to any one of claims 1 to 3, characterized in that: include: Adding the elastic material solution to the acrylic polymer solution, mixing evenly, and keeping the mixture warm, so that the elastic material self-assembles on the surface of the acrylic polymer to obtain the polymer microspheres; Alternatively, the monomer corresponding to the elastic material is added to an acrylic polymer solution, mixed evenly, and kept warm to allow the monomer to polymerize on the surface of the acrylic polymer to form the elastic material, thereby obtaining the polymer microspheres.
5. The method for preparing polymer microspheres according to claim 4, characterized in that: At least one of the following conditions is met: A. The mass ratio of the elastic material to the acrylic polymer is (0.1-1):10; Optionally, the mass ratio of the elastic material to the acrylic polymer is (0.1-0.5):10; B. The mass ratio of the monomer corresponding to the elastic material to the acrylic polymer is (0.1-1):10; C. The insulation temperature is 30°C to 100°C.
6. The method for preparing polymer microspheres according to claim 4, characterized in that: The elastic material further comprises introducing a pore-forming agent during the self-assembly process on the acrylic polymer surface, and the preparation method satisfies at least one of the following conditions: A. The pore forming agent is carbon dioxide; Optionally, the flow rate of the carbon dioxide is 10 to 100 mL / min; Further optionally, the flow rate of the carbon dioxide is 10 to 50 mL / min; B. The mass ratio of the elastic material to the acrylic polymer is (0.1-2):
10.
7. A composite diaphragm, characterized in that: The invention comprises a substrate and a coating arranged on the substrate, wherein the raw material of the coating comprises the polymer microspheres as claimed in any one of claims 1 to 3.
8. The composite diaphragm according to claim 7, characterized in that: The slurry for preparing the coating comprises, by weight: 5-50 parts of the polymer microspheres, 0.1-15 parts of a binder, 0-5 parts of a dispersant, and 0.01-5 parts of a wetting agent; The composite diaphragm satisfies at least one of the following conditions: A. The substrate comprises at least one of polyethylene, polypropylene, polyimide, aramid, and cellulose; B. The adhesive comprises at least one of polyacrylonitrile, styrene-butadiene rubber, sodium hydroxymethyl cellulose, polyvinyl alcohol, polyacrylic acid, polyacrylate, and polyacrylamide; C. the dispersant comprises at least one of ammonium polyacrylate, sodium hexametaphosphate, and sodium pyrophosphate; D. the wetting agent comprises at least one of alkyl sulfate, sulfonate, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether and organosiloxane; E. The coating preparation method includes at least one of spraying, spot coating and roller coating.
9. A battery, characterized in that: It comprises a pole piece and a composite diaphragm as claimed in claim 7 or 8 bonded to the pole piece.
10. The battery according to claim 9, characterized in that The bonding temperature of the pole piece and the composite diaphragm is above 15°C.